Criminal-Legal Protection of Patent Law - Jovašević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
Since 2006, when new criminal legislation came into force, and when new patent legislation came into force, the level of individual, collective and criminal legal protection of copyright and related rights has been upgraded in a qualitative sense. Following other comparative legislations as role models, as well as the standards proclaimed by international legal documents, the Criminal Code categorized (for the first time in our country) all criminal offences representing violations or endangerments of copyright and related rights (that are covered by the term "intellectual property rights") in a separate chapter (Chapter 20) entitled as: "Criminal Offences against Intellectual Property". New legislative solutions are based upon the provisions of the new Law on patents adopted in 2004. Last year, the National Parliament of the Republic of Serbia ratified two international law acts for the protection of intellectual property. These are: 1) Treaty of Patent Law from 2000. year and 2) the Convention of Europe’s patent from 1973. year. These international acts have defined notions, contents, characteristics and the role of patent (and European patent), and their way, proceeding and conditions of notification and the system with organs for protection of patents. In these ways, our state organs are obliged to bring new laws for the establishment of international and European standards in patent law and the social system of the Republic of Serbia. In this paper, the author has analysed these international acts (treaties and conventions), their solutions and the system of criminal law protection to patent law. This paper discusses the definition, the characteristics and the features of the most significant criminal offence by which patent rights (material as well as immaterial or moral rights) are violated or endangered – Injury of Patent law (from Paragraph 201 of the Criminal Code) from theoretical as well as from practical aspects.